Statistical analysis of discontinuities in solar wind ace data and comparison with intermittent mhd turbulence - Greco, A. (2009)
The comparison between Advanced Composition Explorer (ACE) solar wind data and simulations of magnetohydrodynamic (MHD) turbulence shows a good agreement in the waiting-time analysis of magnetic field increments. Similarity between classical discontinuity identification and intermittency analysis suggests a dynamical connection between solar wind discontinuities and intermittent MHD turbulence. Probability distribution functions of increments in ACE data and in simulations reveal a robust structure consisting of small random currents, current cores, and intermittent current sheets. This adds to evidence that solar wind magnetic structures may emerge fast and locally from MHD turbulence. © 2009. The American Astronomical Society. All rights reserved..